Role of international law of the internal criminal law of the CIS countries establishing guilty responsibility in formation - Marin, N.; Ualieva, Zh. (Вестник Карагандинского университета, 2016)
The task of this article includes the analysis of basic provisions of the international criminal law and consid- eration of single questions of its application in the Commonwealth countries. Also in article the attention is paid to the questions connected with definition of a role of norms of the international criminal law in system of the national legislation of countries of the Commonwealth of Independent States and the assessment of extent of influence of these norms on formation of internal criminal law of data of the states is given.
Keywords: international law; international treaties; national law; sources of law; implementation; implement